Philosophical meaning of the myth of pregnant and nursing mothers at Dawuhan village, Banyumas - Astiana Ajeng Rahadini; Rahmat Rahmat (Universitas Islam Sultan Agung, 2018)
Traditional culture underlying a wide range of behavior and deeds of a society and gave birth to a variety of oral literature as well as myth. The myth that developed and still surviving in public life of Java among other myths related to pregnant and nursing mothers. This research is under a descriptively qualitative method supported by field research method along with un-depth interviews in Dawuhan village of Banyumas which is the village where the ancestors of Banyumas was buried. Through field observation and research method of interview to the trusted resource in Dawuhan village was obtained by results of research regarding the myth of pregnant and nursing mothers. This research finds some kinds of myths in relation to recommending and prohibition to perform an action that may harm the fetus, while the myth of breastfeeding mothers mostly prohibition and advice about foods that are consumed by the mother breastfeeding can harm the health of the baby.